Understanding Perinatal Mortality Causes in Indramayu Indonesia - Sukriani, Wahidah; Hilmanto, Dany; Susanto, Herman (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Perinatal mortality is a useful indicator for assessing pregnancy and delivery care. Indramayu was the fourth-highest perinatal mortality in West Java province in 2015. The cause of death can be prevented from several factors including health workers, patients, referrals, and the availability of healthcare facilities. This study aimed to analyze the causes of perinatal mortality in Indramayu. The Study found 375 perinatal deaths but only 296 cases have documents according to the inclusion criteria. Statistical analysis showed there was an association between maternal disease and referral delays with preventable perinatal mortality (p≤0.05). Maternal disease in Indramayu cannot early be detected due to the lack of antenatal care services and behavioral factors on choosing a helper contributed to referral delays. It is necessary to improve the quality of antenatal care services by doing minimum standard of antenatal care for early detection of maternal disease and improving health promotion about danger sign of pregnancy and choosing birth attendants to reduce referral delays.